Overcoming consent form obstacles in qualitative research - Thomson, Stanley Bruce (My University, 2013)
The quality of the researcher’s data is the cornerstone of research excellence. In qualitative research the connection that is established between the researcher and the participants dictates the quality and quantity of the data. The consent form is a necessary part of social science research involving human subjects and can be utilized as a tool to establish trust. The appearance of the document, the language used and amount of time given to read the document affect the level of understanding of the participant. This paper proposes that researchers avoid legalese, aim the language of the documents at the population one is trying to attract, allow sufficient time to read, listen or view the information and provide an opportunity for potential participant feedback. By being open and forthcoming to participants researchers will receive the same from participants and achieve their research data collection goals.
Keywords: consent forms; explanatory statements